Nuclear PTEN safeguards pre-mRNA splicing to link Golgi apparatus for its tumor suppressive role - Shao-Ming Shen (Nature Portfolio, 2018)
Cytoplasmic PTEN is a tumor suppressor that antagonises PI3K signalling. Here, the authors show that nuclear PTEN can interact with the spliceosomal proteins and drive pre-mRNA splicing in a phosphatase-independent manner, in particular, PTEN depletion promotes Golgi extension and secretion through GOLGA2 exon skipping.